Gender Differences in Mental Health Responses of Health Workers During the Covid-19 Pandemic: A Systematic Review with Meta-Analysis - Riyesti Hero Fresna; Shinta Nur Atikah; Muna Maimunah Salsabila; Pringga Widya Pusparini; Ratih Hermas Purnasari; Riski Anisa; Feny Oktaviyani; Ruliany Yuni Nurul Hakim; Muhammad Husein Syawaludin; Syndia Puspitasari (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: The Covid-19 pandemic caused great stress, especially for health workers which resulted in moderate or severe symptoms of depression, anxiety, insomnia, and more serious stress. Gender is very influential, given the differences in biological and social roles between men and women. Gender differences between men and women allow for variations in strategies in responding to mental health to increase awareness and self-management, so as to avoid mental health problems during the Covid-19 pandemic.Subjects and Method: Meta-analysis was performed by searching articles from Google Scholar, PubMed, Scopus, Springer Link, and health-related databases. The keywords used in the article search were